Posted by **Marina** on Wednesday, September 18, 2013 at 6:08pm.

If lim(f+g)=1 as x-->a

and lim(f-g)=1 as x-->a

find lim fg as x-->a

## Answer This Question

## Related Questions

- Calculus - Find the following limits algebraically or explain why they donâ€™t ...
- calc - need to find: lim as x -> 0 of 4(e^2x - 1) / (e^x -1) Try splitting ...
- Calculus - Find the limit. lim 5-x/(x^2-25) x-->5 Here is the work I have so ...
- calculus - f(x)= 3x+2, x<0 3, x=0 x^2+1, x>0 g(x)= -x+3, x<1 0, x=1 x^2...
- CALCULUS - Evaluate each of the following. (a) lim x->0(e^x)-1-x/ x^2 (b) lim...
- Calculus - Find the indicated limits. If the limit does not exist, so state, or ...
- Calculus - Find the indicated limits. If the limit does not exist, so state, or ...
- Math(calculus) - Evaluat d 4lowing1.lim x/|x| x-->0 2.lim x->1 sqrt(x^2+2...
- math - i need some serious help with limits in pre-calc. here are a few ...
- Calc. Limits - Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/0...

More Related Questions